2012
DOI: 10.1097/01.sa.0000412405.44628.cd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenylephrine and Ephedrine Bolus Treatment on Cerebral Oxygenation in Anaesthetized Patients

Abstract: Editor's key points † Effects of different vasopressor agents on cerebral oxygenation have been unclear. † Ephedrine and phenylephrine, used for intraoperative hypotension, were investigated in a cross-over design study. † Phenylephrine, but not ephedrine, decreased cardiac output (CO) and brain oxygenation. † This study highlights the importance of CO in preserving brain oxygenation during management of intraoperative hypotension.Background. How phenylephrine and ephedrine treatments affect global and regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 21 publications
1
31
2
Order By: Relevance
“…Using NIRS technology, Meng et al 19 demonstrated decreased cerebral oxygenation during anesthesia when administering boluses of phenylephrine and unaltered cerebral oxygenation when administering boluses of ephedrine. Brassard et al 8 found reduced cerebral oxygenation with increasing doses of NE in healthy volunteers; however, in the study presented here, NE was administered to maintain a fixed MAP, whereas MAP and systemic vascular resistance substantially increased in Brassard et al's study.…”
Section: Discussionmentioning
confidence: 98%
“…Using NIRS technology, Meng et al 19 demonstrated decreased cerebral oxygenation during anesthesia when administering boluses of phenylephrine and unaltered cerebral oxygenation when administering boluses of ephedrine. Brassard et al 8 found reduced cerebral oxygenation with increasing doses of NE in healthy volunteers; however, in the study presented here, NE was administered to maintain a fixed MAP, whereas MAP and systemic vascular resistance substantially increased in Brassard et al's study.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, between the baseline and BC1 V MCA values, patients received fluids and vasopressors to control hypotension. It has been suggested that ephedrine did not modified cerebral blood flow (SctO 2 and V MCA ), whereas phenylephrine may decrease it in anesthetized patients [18,19]. However, in the present study, only 8 (15%) of patients received phenylephrine.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, changes in the NIRO-200NX derived frontal lobe oxygenation Table 1 Changes from baseline AE95% confidence interval for haemodynamic variables during hyperventilation (HYP), whole-body heating (WBH), administration of noradrenaline, without and with petCO 2 -correction (0Á15 lg kg À1 min À1 ) (NA; NA+CO 2 ), administration of phenylephrine (0Á12 lg kg À1 min À1 ) (PE), 40°head-up tilt, without and with administration of phenylephrine (HUT; HUT+PE). With elevation of blood pressure, vasopressor agents (except for ephedrine) have a negative impact on a SR-NIRSbased evaluation of S c O 2 in both awake and anesthetised humans (Brassard et al, 2009;Lucas et al, 2010;Nissen et al, 2010;Meng et al, 2011). While sympathetic innervation of the cerebral arteries is described (Nelson & Rennels, 1970), the role of sympathetic activity for regulation of CBF remains debated (Zhang et al, 2002;Mitchell et al, 2009).…”
Section: Discussionmentioning
confidence: 97%